1991
DOI: 10.1677/jme.0.0070131
|View full text |Cite
|
Sign up to set email alerts
|

The dopamine D2 receptor is expressed in GH3 cells

Abstract: Some pituitary tumours respond to dopamine by decreasing the release of prolactin and/or GH and by inhibition of tumour growth. Certain tumours are unresponsive. Dopamine D2 receptor high-affinity binding is impaired in these tumours, and the rat GH3 cell line behaves in a similar way. The hypothesis that the dopamine-binding defect results from impaired D2 receptor gene expression has been tested in the present study. On Northern blots, D2 receptor mRNA was present in both normal rat pituitary cells and in GH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…This finding may well account for all of the observed effects of bromocriptine in this study, and is in agreement with the results obtained by Johnston et al [5], who demonstrated that the D 2 R is expressed in GH 3 cells. However, the amount of D 2 Rs per cell was reduced compared with normal controls and they only showed low-affinity binding characteristics [4,5].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This finding may well account for all of the observed effects of bromocriptine in this study, and is in agreement with the results obtained by Johnston et al [5], who demonstrated that the D 2 R is expressed in GH 3 cells. However, the amount of D 2 Rs per cell was reduced compared with normal controls and they only showed low-affinity binding characteristics [4,5].…”
Section: Discussionsupporting
confidence: 94%
“…GH 3 cells lack high affinity DA binding sites [4], but they still express D 2 R mRNA as identified by Nothern blot analysis [5]. In addition, the putative D 2 R protein was identified in GH 3 cell membrane preparations subjected to SDS-PAGE analysis [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat ovarian tissue RNA was utilized as a positive control. The GH3 cells expressed SSTRs including all of SSTR1, 2, 3, 4, and 5 and dopamine receptor D2R as reported previously (Johnston et al 1991, Yang et al 2005. The expression level of SSTR2 in GH3 cells was relatively high when compared with that in rat pituitary tissues, while D2R transcript was comparably low in GH3 cells.…”
Section: Resultssupporting
confidence: 78%
“…In GH3 cells, D2R expression is not well established [23, 24] and it has been shown that exposing cells to growth factors (i.e. EGF or NGF) induces the expression of functional D2R [25].…”
Section: Resultsmentioning
confidence: 99%